2015
DOI: 10.1186/s12860-015-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

α6β1- and αV-integrins are required for long-term self-renewal of murine embryonic stem cells in the absence of LIF

Abstract: BackgroundThe growth properties and self-renewal capacity of embryonic stem (ES) cells are regulated by their immediate microenvironment such as the extracellular matrix (ECM). Integrins, a central family of cellular ECM receptors, have been implicated in these processes but their specific role in ES cell self-renewal remains unclear.ResultsHere we have studied the effects of different ECM substrates and integrins in mouse ES cells in the absence of Leukemia Inhibitory Factor (LIF) using short-term assays as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Indeed, such a hypothesis is supported by the observation that removal of either β1 or αv integrin affects the ability of ESC to exit from the pluripotent state, as demonstrated by their retention of the expression of pluripotency markers. This is consistent with previous data showing a role for αv integrin in human ESC function and a role for αv integrin in maintaining the epistem cell‐like state in mESC cultures . Moreover, α5β1 integrin has a role in hESC function through adhesion to fibronectin .…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, such a hypothesis is supported by the observation that removal of either β1 or αv integrin affects the ability of ESC to exit from the pluripotent state, as demonstrated by their retention of the expression of pluripotency markers. This is consistent with previous data showing a role for αv integrin in human ESC function and a role for αv integrin in maintaining the epistem cell‐like state in mESC cultures . Moreover, α5β1 integrin has a role in hESC function through adhesion to fibronectin .…”
Section: Discussionsupporting
confidence: 93%
“…Regulation of LIF through integrins or FAK was previously unknown. In the absence of LIF, laminin-111 and -511 (laminin-511 is composed of α5, β1 and γ1 chains) promote stem cell renewal in vitro through α6β1 integrin (Cattavarayane et al, 2015). This might involve induction of LIF, since it is widely used to maintain self-renewal.…”
Section: Discussionmentioning
confidence: 99%
“…Looking in more detail at the expression of key signaling pathway components, we found that the LIF-Stat3, PI3K-Akt, Nodal-Smad2/3, and Wnt signaling pathways were all significantly activated in NHSMV cells ( Figure S2D). ECM components can also affect the growth and self-renewal properties of ESCs (Cattavarayane et al, 2015), and we found that a number of ECM molecules, including collagen, integrin, laminin, tenascin, and THBS, were significantly upregulated in NHSMV cells ( Figure S2E). Finally, analysis of PI3K-Akt signaling pathways showed upregulated GT-RTK, ECM-ITGA, Gbg, and Cytokine R and downregulated PP2A (promoting CDK activation and cell-cycle progression) in NHSMV cells ( Figure S2F).…”
Section: Culture Conditions Affect the Gene Expression Profile Of Cescsmentioning
confidence: 93%